2015
DOI: 10.1002/gps.4355
|View full text |Cite
|
Sign up to set email alerts
|

Apolipoprotein E and Clusterin can magnify effects of personality vulnerability on declarative memory performance in non‐demented older adults

Abstract: Objectives Recent research has linked psychological (personality) factors and specific genetic risk polymorphisms to performance on neurocognitive phenotypes. We examined whether episodic or semantic memory performance is associated with (a) three personality traits (i.e., neuroticism, extraversion, openness to experience), (b) two neurodegenerative-related polymorphisms (i.e., Apolipoprotein E (APOE; rs7412; rs429358), Clusterin (CLU; rs11136000)), and (c) cross-domain risk interactions (magnification effects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 59 publications
0
11
0
Order By: Relevance
“…In healthy young adults, CLU allelic risk had lower white matter integrity than their counterparts [33] which may indicate an increased risk for developing dementia in old age. CLU is also similar in structure with the molten globule structure of APOE and they may influence each other in frontal lobe regions [10,34,35]. …”
Section: Introductionmentioning
confidence: 99%
“…In healthy young adults, CLU allelic risk had lower white matter integrity than their counterparts [33] which may indicate an increased risk for developing dementia in old age. CLU is also similar in structure with the molten globule structure of APOE and they may influence each other in frontal lobe regions [10,34,35]. …”
Section: Introductionmentioning
confidence: 99%
“…Results from other studies on the APOE -by-neuroticism interaction suggest that the specific cognitive domains studied should also be considered. Sapkota et al found the APOE -by-neuroticism interaction did not predict baseline or subsequent change in declarative memory [ 24 ]. Chapman et al found an overall APOE -by-neuroticism interaction in a multivariate analysis of variance with five cognitive domains as outcomes [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Only one of three studies that used multiple, more challenging cognitive tests to measure cognition reported that depressive symptoms were more strongly related to cognition in E4 carriers ([ 21 ], cf. [ 22 24 ]). Regarding neuroticism, in the Ginkgo Evaluation of Memory sample neuroticism has a greater negative association with cognitive ability [ 25 ] and subsequent cognitive decline [ 26 ] in E4 carriers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, increased plasma apoJ levels in MCI indicated an amplified risk of further cognitive decline. Furthermore, it was shown that genetic variation in the CLU region may amplify the influence of personality type on the performance of declarative memory in older, non-demented adults [71].…”
Section: Clu Apolipoprotein J (Apoj)mentioning
confidence: 99%